2014
DOI: 10.1111/gbb.12121
|View full text |Cite
|
Sign up to set email alerts
|

A variant in ANKK1 modulates acute subjective effects of cocaine: a preliminary study

Abstract: This study aimed to evaluate whether functional variants in the ankyrin repeat and kinase domain-containing 1 gene (ANKK1) and/or the dopamine receptor D2 gene (DRD2) modulate the subjective effects (reward or non-reward response to a stimulus) produced by cocaine administration. Cocaine-dependent participants (N = 47) were administered 40 mg of cocaine or placebo at time 0, and a subjective effects questionnaire (visual analog scale) was administered 15 minutes prior to cocaine administration, and at 5, 10,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…These have been assessed in prior studies (Nielsen et al, 2012a; Kosten et al, 2013b,a; Spellicy et al, 2013; Kosten et al, 2013b, 2014; Anastasio et al, 2014; Spellicy et al, 2014; Frazier et al, 2014; Liu et al, 2014; Brewer III et al, 2015). This includes several polymorphisms in the dopamine and serotonin transporters, and in the norepinephrine postsynaptic receptor.…”
Section: Motivating Datamentioning
confidence: 99%
“…These have been assessed in prior studies (Nielsen et al, 2012a; Kosten et al, 2013b,a; Spellicy et al, 2013; Kosten et al, 2013b, 2014; Anastasio et al, 2014; Spellicy et al, 2014; Frazier et al, 2014; Liu et al, 2014; Brewer III et al, 2015). This includes several polymorphisms in the dopamine and serotonin transporters, and in the norepinephrine postsynaptic receptor.…”
Section: Motivating Datamentioning
confidence: 99%
“…Congruent with previously published studies from our laboratory (Brewer et al , 2015, Spellicy et al , 2014), a double-blind, placebo-controlled, within-subjects experimental design was used. Participants were randomized and intravenously administered 0 mg (saline) or 40 mg of cocaine in the morning or afternoon.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Our laboratory previously reported that the subjective effects of cocaine use are moderated, in part, by variants in the ankyrin repeat and kinase domain-containing 1 ( ANKK1 ) (Spellicy et al , 2014), dopamine transporter (DAT1 , SLC6A4), and serotonin transporter (SLC6A4) 5-HTTLPR (Liu et al , 2015) genes. Herein, we continue to investigate the relation between genetic variants and subjective effects of cocaine by exploring the role of the serotonergic system in the subjective effects of cocaine use in non-treatment seeking cocaine-dependent individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[30] DNA was isolated from blood using the Gentra Puregene Blood Kit (Qiagen, Germantown, MD) following the manufacturer’s recommendations. ADRA1A genotype was determined using 5’-fluorogenic exonuclease assays (TaqMan ® , Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…[30,31] As part of this larger study, and in order to further identify genetic subgroups in which there is enhanced response to cocaine administration in the laboratory, this present study examined whether the rs1048101 polymorphism enhances the subjective effects produced by cocaine in a group of cocaine-dependent individuals. We hypothesized that CC homozygotes for rs1048101 would report higher ratings of cocaine-induced subjective effects in the laboratory.…”
Section: Introductionmentioning
confidence: 99%